A global view of network of lncRNAs and their binding proteins. Issue 2 (8th December 2014) - Shang, Desi; Yang, Haixiu; Xu, Yanjun; Yao, Qianlan; Zhou, Wenbin; Shi, Xinrui; Han, Junwei; Su, Fei; Su, Bin; Zhang, Chunlong; Li, Chunquan; Li, Xia
Abstract : A network of lncRNAs and their binding proteins provided insights into understanding lncRNA functions. Abstract : Recently, the long non-coding RNAs (lncRNAs) have obtained wide attention because they have broad and crucial functions in regulating complex biological processes. Many lncRNAs functioned by interfacing with corresponding RNA binding proteins and the complexity of lncRNAs' function was attributed to multiple lncRNA–protein interactions. To gain insights into the global relationship between lncRNAs and their binding proteins, here we constructed a lncRNA–protein network (LPN) based on experimentally determined functional interactions between them. This network included 177 lncRNAs, 92 proteins and 683 relationships between them. Cluster analysis of LPN revealed that some proteins (such as AGO and IGFBP families) and lncRNA (such as XIST and MALAT1) were densely connected, suggesting the potential co-regulated mechanism and functional cross-talk of different lncRNAs. We then characterized the lncRNA functions and found that lncRNA binding proteins (LBPs) enriched in many cancer or cancer-related pathways. Finally, we investigated the different topological properties of LBPs in PPIs network. Compared with disease proteins and average ones, LBPs tend to have significantly higher degree, betweenness, and closeness but a relatively lower clustering coefficient, indicating their centrality and essentiality in the context of a biological network.